2015
DOI: 10.1155/2015/497462
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Medium for Extracellular Lipase Production fromAspergillus nigerUsing Response Surface Methodology

Abstract: Lipase produced by Aspergillus niger is widely used in various industries. In this study, extracellular lipase production from an industrial producing strain of A. niger was improved by medium optimization. The secondary carbon source, nitrogen source, and lipid were found to be the three most influential factors for lipase production by single-factor experiments. According to the statistical approach, the optimum values of three most influential parameters were determined: 10.5 g/L corn starch, 35.4 g/L soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…The F-value of 58.97 indicates that the model is significant and the Lack of Fit (LOF) F-value of 2.56 is insignificant. A coefficient of determination (R 2 ) closer to 1 indicates a better correlation between the predicted and observed values, and a smaller coefficient of variation (C.V.%) implies a higher reliability of the experiment [35,44]. In this study, the R 2 of 0.9823, predicted R of 0.9538 and adjusted R of 0.9826 were consistent, and the predicted R and adjusted R were within 0.20 of each other.…”
Section: Optimization By Rsmsupporting
confidence: 65%
See 1 more Smart Citation
“…The F-value of 58.97 indicates that the model is significant and the Lack of Fit (LOF) F-value of 2.56 is insignificant. A coefficient of determination (R 2 ) closer to 1 indicates a better correlation between the predicted and observed values, and a smaller coefficient of variation (C.V.%) implies a higher reliability of the experiment [35,44]. In this study, the R 2 of 0.9823, predicted R of 0.9538 and adjusted R of 0.9826 were consistent, and the predicted R and adjusted R were within 0.20 of each other.…”
Section: Optimization By Rsmsupporting
confidence: 65%
“…The main nutrients in the fermentation medium were of carbon (beef extract) and nitrogen (NH 4 NO 3 ) sources. The fermentation biomass depended on the carbon/nitrogen (C/N) ratio and was generally promoted by a higher C/N ratio [34,35]. The experiments showed that Pseudomonas sp.…”
Section: Effects Of Fermentation Conditions On the Growth Of Pseudomomentioning
confidence: 99%
“…AB570425.1, protein molecular weight: 31.57 kDa) from Aspergillus niger strain CICC2475 (Jia et al 2015) Lipase activity was as follows: A, 19 555 U/g; B, 30 429 U/g; C, 21 747 U/g; D, 31 659 U/g. AB570425.1, protein molecular weight: 31.57 kDa) from Aspergillus niger strain CICC2475 (Jia et al 2015) Lipase activity was as follows: A, 19 555 U/g; B, 30 429 U/g; C, 21 747 U/g; D, 31 659 U/g.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…It is widely used to identify effective factors, study interactions, select optimum conditions and quantify the relationships between one or more measured responses and the vital input factors in a limited number of experiments [11,30]. Furthermore, RSM has been successfully applied to evaluate and optimize the effect of process parameters in the production of lipase [28,31,32]. A central composite design (CCD) is the most commonly used response surface design when the experimental design is defined by the upper and lower limits of each parameter [16,33].…”
Section: Introductionmentioning
confidence: 99%